Secondary analysis of outcomes after 11,085 hip fracture operations from the prospective UK Anaesthesia Sprint Audit of Practice (ASAP-2) - White, S.M.; Moppett, I.K.; Griffiths, R.; Johansen, A.; Wakeman, R.; Boulton, C.; Plant, F.; Williams, A.; Pappenheim, K.; Majeed, A.; Currie, C.T.; Grocott, M.P.W. (Wiley, 2016)
We re-analysed prospective data collected by anaesthetists in the Anaesthesia Sprint Audit of Practice (ASAP-1) to describe associations with linked outcome data. Mortality was 165/11,085 (1.5%) 5 days and 563/11,085 (5.1%) 30 days after surgery and was not associated with anaesthetic technique (general vs. spinal, with or without peripheral nerve blockade). The risk of death increased as blood pressure fell: the odds ratio (95% CI) for mortality within five days after surgery was 0.983 (0.973–0.994) for each 5 mmHg intra-operative increment in systolic blood pressure, p = 0.0016, and 0.980 (0.967–0.993) for each mmHg increment in mean pressure, p = 0.0039. The equivalent odds ratios (95% CI) for 30-day mortality were 0.968 (0.951–0.985), p = 0.0003 and 0.976 (0.964–0.988), p = 0.0001, respectively. The lowest systolic blood pressure after intrathecal local anaesthetic relative to before induction was weakly correlated with a higher volume of subarachnoid bupivacaine: r2 −0.10 and −0.16 for hyperbaric and isobaric bupivacaine, respectively. A mean 20% relative fall in systolic blood pressure correlated with an administered volume of 1.44 ml hyperbaric bupivacaine. Future research should focus on refining standardised anaesthesia towards administering lower doses of spinal (and general) anaesthesia and maintaining normotension.